Ownership Structure, Corporate Governance and Dividend Performance on the Ghana Stock Exchange - Bokpin, G. A. (Emerald Group Publishing Limited, 2011)
Purpose – This paper aims to document the interaction between ownership structure, corporate governance and dividend performance on the Ghana Stock Exchange (GSE). Design/methodology/approach – Panel data covering a period from 2002 to 2007 for 23 firms were analyzed within the framework of fixed effects techniques. Findings – The paper reports that foreign share ownership significantly, positively, influences dividend payment among firms on the GSE. It found board size to have a statistically positive effect on dividend payment among the corporate governance variables. It did not, however, find a significant relationship between inside ownership, board independence, board intensity, CEO duality and dividend performance. The results also indicate that highly leveraged firms will significantly reduce dividend payments. Finally, age and income volatility were found to be significant determinants of dividend performance on the GSE. Originality/value – The paper considers a much broader approach to investigating the impact of ownership structure and corporate governance on dividend performance on the GSE, a marked departure from other studies conducted on the GSE.
Keywords: corporate ownership; Corporate governance; Stock exchanges; dividends; Ghana